1986
DOI: 10.1083/jcb.102.4.1344
|View full text |Cite
|
Sign up to set email alerts
|

Identification and further characterization of the specific cell binding fragment from sponge aggregation factor.

Abstract: Abstract. Monoclonal antibodies (McAbs) were raised against the aggregation factor (AF) from the marine sponge Geodia cydonium. Two clones were identified that secrete McAbs against the cell binding protein of the AF complex. Fab fragments of McAbs: 5D2-D11 completely abolished the activity of the AF to form secondary aggregates from single cells. The McAbs were determined to react with the AF in vitro; this interaction was prevented by addition of the aggregation receptor, isolated and purified from the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 29 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…PAGE was performed in 10~ slab gels in the presence of 0.1 ~ SDS as described by Laemmli (1970). The separated proteins were transferred to nitrocellulose sheets according to the method described by Towbin et al (1979) with the modifications given by Gramzow et al (1986). The sheets were incubated with anti-La MAb or monospecific anti-La antibodies; the immunocomplexes that formed were visualized by incubation with a 1 : 500 dilution of either peroxidase-conjugated anti-mouse IgG or peroxidaseconjugated anti-human IgG using the 4-chloro-1-naphthol/hydrogen peroxide procedure (Nakane, 1968).…”
Section: Methodsmentioning
confidence: 99%
“…PAGE was performed in 10~ slab gels in the presence of 0.1 ~ SDS as described by Laemmli (1970). The separated proteins were transferred to nitrocellulose sheets according to the method described by Towbin et al (1979) with the modifications given by Gramzow et al (1986). The sheets were incubated with anti-La MAb or monospecific anti-La antibodies; the immunocomplexes that formed were visualized by incubation with a 1 : 500 dilution of either peroxidase-conjugated anti-mouse IgG or peroxidaseconjugated anti-human IgG using the 4-chloro-1-naphthol/hydrogen peroxide procedure (Nakane, 1968).…”
Section: Methodsmentioning
confidence: 99%
“…The homogeneity of the antigen preparations was proven by NaDodSO4/gel electrophoresis, and their specificities, by immunoblotting (12) with standardized reference antisera (anti-Ro and anti-La; Centers for Disease Control, Atlanta). General procedures for preparation of mAbs (12,13) …”
Section: Introductionmentioning
confidence: 99%
“…The homogeneity of the antigen preparations was proven by NaDodSO4/gel electrophoresis, and their specificities, by immunoblotting (12) with standardized reference antisera (anti-Ro and anti-La; Centers for Disease Control, Atlanta). General procedures for preparation of mAbs (12,13) (12). In a further step, the antibodies were purified by immunoaffinity column chromatography using normal anti-mouse IgG coupled to Sepharose 4B (14).…”
mentioning
confidence: 99%
“…This finding was our first evidence that calelectrin is present extracellularly in this organism. Next, we studied whether calelectrin is associated with G. cydonium AF, which is known to be composed of a series of polypeptides among which is the cell binding fragment (Gramzow et al, 1986). Then it was shown that the AF particles also contained a protein with an M, of 32,000 that was recognized in the immunoblot by antibodies against calelectrin (Figure 3 For further proof that the 32 kd polypeptide in the AF particle that reacted with anticalelectrin is presumably calelectrin, inhibition studies were performed.…”
Section: Resultsmentioning
confidence: 99%